Changes in ascorbic acid and total phenolics contents associated with browning inhibition of pineapple slices - AYÓN-REYNA,Lidia Elena (2019)
Abstract Pineapple slices were treated with three antioxidants and stored under passive modified atmosphere packaging (MAP) to evaluate the effect of these treatments on tissue browning (percentage of dark area) and the accumulation of ascorbic acid and total phenolics. Pineapple slices were immersed in ascorbic acid (AA), isoascorbic acid (IAA), and N-acetylcysteine (NAC) solutions for 2 min, and then were packed and stored at 5 °C under air (AIR) or MAP for 15 days. Water was used as control. The application of IAA and NAC under passive MAP reduced better the tissue browning index and maintained a good quality of the slices. The use of AA and IAA increased the contents of ascorbic acid and total phenolics. The application of IAA followed by storage under MAP conditions was effective in reducing tissue browning, which was associated with a higher retention of ascorbic acid and total phenolics contents of the pineapple slices.